1980
DOI: 10.3758/bf03329541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enclosure size on activity and sleep of a hystricomorph rodent (Octodon degus)

Abstract: Eight adult and eight infant degus were continuously observed over two 24-h sessions in order to determine the effects of large vs. small enclosure size on the stability of activity and sleep cycles. Behaviors were categorized into one of five mutually exclusive categories. Although the proportion of time spent engaging in sleep and other activities was not found to vary significantly, the circadian placement of activities by age and sex class was found to be altered as a function of enclosure size. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…As referred to the pecking behaviour, according to Newberry et al, (2007), in the wild, pecking is a natural behaviour that leads to the establishment of a pecking order in the group. While for the abnormal behaviours, captive environments can cause abnormality and several studies have already shown the effect of enclosure size in the behaviour of captive animals (Fisher at al., 1980;Estep et al, 1978;Innis et al, 1985;Hogan et al, 1988;Jensvold et al, 2001). Among of the examples are feather-pecking, toe and face pecking, anorexia and many others.…”
Section: Introductionmentioning
confidence: 99%
“…As referred to the pecking behaviour, according to Newberry et al, (2007), in the wild, pecking is a natural behaviour that leads to the establishment of a pecking order in the group. While for the abnormal behaviours, captive environments can cause abnormality and several studies have already shown the effect of enclosure size in the behaviour of captive animals (Fisher at al., 1980;Estep et al, 1978;Innis et al, 1985;Hogan et al, 1988;Jensvold et al, 2001). Among of the examples are feather-pecking, toe and face pecking, anorexia and many others.…”
Section: Introductionmentioning
confidence: 99%